2020
DOI: 10.3390/brainsci10030189
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Memory in Depression: State and Trait Differences between Bipolar and Unipolar Disorders

Abstract: Background: Changes in olfactory recognition memory may constitute sensory markers in depression. Significant differences may exist between unipolar and bipolar depression. Our study compares olfactory memory between control, unipolar, and bipolar patients in depressed and euthymic states in order to identify potential markers of depression. Methods: 176 participants were recruited in 5 groups: depressed bipolar (DB), euthymic bipolar (EB), depressed unipolar (DU), euthymic unipolar (EU), and controls (HC). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In Experiment 2, we compared OI and OS between patients with BD, MDD and SCZ and found impaired olfactory function in all patient groups, with SCZ patients showing the worst performance in both olfactory function tests, except normal OS in euthymic BD patients. The lack of differences in olfactory function between depressed BD and MDD patients is in accordance with previous reports (Kamath et al, 2018; Kazour et al, 2020; Swiecicki et al, 2009). Recent imaging studies indicate that compared to BD, SCZ patients show a greater reduction in grey matter volume in the frontal-temporal cortex, hippocampus and amygdala (Maggioni et al, 2016; Nenadic et al, 2015), which are involved in olfactory processing.…”
Section: Discussionsupporting
confidence: 93%
“…In Experiment 2, we compared OI and OS between patients with BD, MDD and SCZ and found impaired olfactory function in all patient groups, with SCZ patients showing the worst performance in both olfactory function tests, except normal OS in euthymic BD patients. The lack of differences in olfactory function between depressed BD and MDD patients is in accordance with previous reports (Kamath et al, 2018; Kazour et al, 2020; Swiecicki et al, 2009). Recent imaging studies indicate that compared to BD, SCZ patients show a greater reduction in grey matter volume in the frontal-temporal cortex, hippocampus and amygdala (Maggioni et al, 2016; Nenadic et al, 2015), which are involved in olfactory processing.…”
Section: Discussionsupporting
confidence: 93%
“…A study on smell recognition in patients with BD and major depression reported that patients with BD depressive episodes and unipolar depression had a greater odor loss compared to control groups. This decreased olfactorious recognition memory persists in euthymic bipolar patients after remission of the depressive episode (Kazour et al 2020 ). Lahera et al reported that the deficiency in odor identification in patients with the euthymic period of BD was permanent and related to permanent cognitive impairment of BD patients in remission (Lahera et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A (disease) marker is either a substance, a measurable parameter, or a physical sign of a disease [ 178 , 179 , 180 , 181 ]. There are two types of markers: trait markers and state markers.…”
Section: Olfaction As a Potential Marker For Dystonia: Further Dirmentioning
confidence: 99%